Effectiveness of Using Silicone Tape for Blepharoptosis in Children - S. A., Boboev; M. Sh., Khakimova (American Journal of Bioscience and Clinical Integrity, 2025)
Blepharoptosis (BP) is a common disease - from 2% to 9% of patients in ophthalmological hospitals (Atamanov V.V. 2003). Drooping of the upper eyelid, along with a significant cosmetic defect, is the cause of decreased vision and the development of amblyopia , due to the forced position of the head leads to curvature of the spine. According to a number of authors, BP ranks first among congenital eyelid pathologies in children and is one of the causes of childhood disability (M.T. Aznabaev , 1965; S.A. Barkhash , L.D. Pikalova, V.P. Khrinenko , 1975; S.A. Barkhash et al ., 1981).